(untitled) (Вестник КазНУ. Серия Экономическая, 2016)
In 2016 been celebrated the 80th anniversary of publication of the work of Keynes’ «General Theory of Employment, Interest and Money». This date are updated by exploration of the phenomenon of labor, forces to search for the answer to the question about the causes of heated discussions that have unfolded around her. Keynes refuted many provisions of the preceding economic science, he has criticized the basic principles of the classical theory. First of all, in contrast to the classical school, he discovers that the market mechanism has no internal self-regulating mechanisms, and demonstrates the need for state regulation of the economy. Keynes changed the methods of studying the economic reality: introduced the macroeconomic approach, take into account the psychological aspects of human behavior, paid much attention to the uncertainty factors and expectations.